Teaching Methods for Keyboard Accompaniment in Worship Songs: A Study at GPII Ebenhaezer Yogyakarta - Febrianto, Yusuf; Samosir, Tanesya Hotris (IAKN Tarutung, 2024)
The limited number of musicians in churches across Indonesia, including GPII Ebenhaezer Yogyakarta, remains a common issue. To address this challenge, this study proposes keyboard teaching as a potential solution. Successful knowledge transfer requires the application of appropriate teaching methods. This research uses a qualitative method with an action research approach, focusing on keyboard teaching at GPII Ebenhaezer Yogyakarta. The sample was selected through purposive sampling, involving three youths as participants. Data collection was carried out through observation, interviews, and documentation, while data analysis followed the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results show that the lecture, demonstration, imitation, drill, and recitation methods are effective in teaching keyboard accompaniment for worship songs. Despite variations in participants' responses and understanding, all achieved the expected learning outcomes.